Terapi Akupresur Terhadap Tekanan Darah pada Penderita Hipertensi: Literature Review - Suryawan, Putri Ayu; Arneliwati, Arneliwati; Jumaini, Jumaini (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2022)
Introduction: Acupressure is a non-pharmacological method of treatment, acupressure therapy is the development of massage therapy that goes participation in participation with the exploitation of acupuncture. The procedure therein remedial programme put into practice digits instead of therapeutic needles made at the same points as those used in acupuncture therapy. Acupressure therapy has many benefits, one of which is to lower your blood pressure. Objective: The objective of the contemplate was to influence the chain reaction of shiatsu remedial programme on parentage coercion in patients with arterial hypertension. Methode: Journal design in the form of literature review. Data sources: google scholar and pubmed. Inclusion criteria: 2016-2020 articles, in Indonesian and English, health journals, discussing suppressing blood pressure for hypertensive patients. Outcome: Based on 5 scientific articles, all articles concluded that hypertensive patients experienced an effect or decrease in blood pressure after using acupressure therapy. Conclusion: Acupressure can lower blood pressure in hypertensive patients.